Metaphysical Conceit Analyses Of Selected Poems By John Donne’s - Aprilia Ridadi Prihatini; Ananda Dewi Sahri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Metaphysical is a literary genre that combines philosophical ideas with emotional depth and deep analyses of nature. One of the famous authors in this genre is John Donne, who is known for his profound themes, distinctive style, and skillful use of conceit in his poetry. This paper aims to explore the influence of John Donne's work on metaphysical poetry and assess the contribution and striking elements of metaphysics in his selected poems by examining Donne's use of conceit. The research aims to examine how John Donne influenced the poetry of metaphysics and explore the assessment of his literary endeavors as well as metaphysical elements. The research has uncovered new perspectives from a metaphysical standpoint on religion, the universe, love, and death.